Simple test of synergy between ampicillin and vancomycin for resistant strains of Enterococcus faecium. - Green, M (1994)
The combination of ampicillin and vancomycin kills some but not all strains of ampicillin- and vancomycin-resistant Enterococcus faecium. We compared a simple test for synergy utilizing a commercially available microdilution susceptibility system with time-kill studies and determined acceptable breakpoints for this test for 20 strains of ampicillin- and vancomycin-resistant E. faecium. The combination of ampicillin and vancomycin was tested for synergy by time-kill, broth macrodilution, and broth microdilution procedures. Repeat testing of isolates by macro- and microdilution synergy methods yielded MICs that were within one twofold dilution of each other for both intra- and intertest comparisons. Synergy was always detected by time-kill studies when the MIC of ampicillin in the combination synergy screen was < or = 8 micrograms/ml in the presence of vancomycin. No synergy was detected when the MIC was > 16 micrograms/ml in the combination microdilution synergy screen. The determination of the synergy by the broth microdilution procedure appears to be simple, convenient, and accurate.